Architectural renovation works of the Deputy Vice-Chancellor's Office (Academic & International) on level 3, Chancellor's Building, Sultan Abdul Jalil Shah Campus (KSAJS), Universiti Pendidikan Sultan Idris, Tanjong Malim, Perak / Muhammad Iqbal Abdullah - Abdullah, Muhammad Iqbal (Universiti Teknologi MARA UiTM,Perak, 2022)
Industrial training is one way to enhances the student on how working in an organization especially in Building Surveying field. We are required to undergo the practical from10 October 2021 until January 2022. Objective of the training is to expose students to the real working environment in the field or industry related to courses taken. In addition, students also have the opportunity to enhance their knowledge and skills in addition to practice what they have learned at the university. This Technical Report is a full report about what student done throughout the practical training.